An empirical study of the impact of multiple modes of delivery on student learning in a blended course. Issue 3 (3rd July 2018) - Baragash, Reem Sualiman; Al-Samarraie, Hosam
ABSTRACT: Finding ways to promote students' online learning performance has always been regarded as a necessity for higher education institutions. In this study, we investigated how certain modes of learning delivery can potentially influence students' learning. Precisely, the effects of Face-to-Face (F2F), Learning Management System (LMS), and Web-based Learning (WBL) on students' online learning were examined. A survey questionnaire, distributed to 196 undergraduate students, was used in this study. The use of these modes showed varied effects on the learning outcomes of students. F2F learning mode was found to influence students' performance in completing online assignments. The result also showed that the use of LMS-based learning mode affects students' performance in the final exam. These results are believed to provide useful directions for the higher education community to better understand how certain modes of learning delivery can be related to the development of students' performance in a blended learning environment.